Internet connectivity disruption in Gambia (Gambia) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Gambia. Data sourced from IODA.
Network Disruption Incident ID: GM-2026-0002. Severity: critical. Confidence: 65%